Assessing current practices in market design to enable e-mobility in Brazil - Valenzuela da Silva, Paula Andrea; Magalhães Gomes, Angela; Nobrega Barroso, Luiz Augusto (My University, 2025)
The electrification of the transport sector will have many implications for the power sector. The latter, however, can benefit from e-mobility as a provider of system flexibility if regulation provides the correct signals for smart charging and interactions between mobility and storage to happen. This paper draws the main conclusions of an analysis focused on how the regulation of electricity distribution utilities in Brazil enables a smart e-mobility business model in the country. The analyses here presented are part of a Research and Development project sponsored by CPFL, a large Brazilian utility, and the conclusions can be useful for other countries with similar characteristics to unlock obstacles to a greater participation of electric vehicles in the transportation fleet, which is also important to reduce the country's CO 2eq emissions.